Management of Online Shopping Determined by COVID-19 in Romania: Array - Bucăța, George (Acta Universitatis Danubius. Œconomica, 2021)
Online commerce was defined by most as the winner of this period, which was marked by the Covid-19 pandemic, when offline stores closed in many sectors, as well as restaurants, cafes and bars, but also schools. The pandemic thus forced the world to digitize itself, and adaptation to the new reality meant the persistence of online shopping behavior. This can also be seen in the numbers. More specifically, data from the National Institute of Statistics show that retail sales through contract houses or via the Internet increased by almost 40% in the first half of 2020 compared to the first half. 2020 compared to 2019. The pace moderated (7-13%) in January and February 2020 (compared to the same months in 2019) and increased to 27% in March 2020 when the state of emergency was declared in mid of year. Month. Then progress galloped, peaking at 75% in April 2020, after which the pace slowed in May and June 2020 without falling below 50%.